Mutations Affecting the SAND Domain of DEAF1 Cause Intellectual Disability with Severe Speech Impairment and Behavioral Problems - Vulto-van Silfhout, Anneke T.; Rajamanickam, Shivakumar; Jensik, Philip J.; Vergult, Sarah; de Rocker, Nina; Newhall, Kathryn J.; Raghavan, Ramya; Reardon, Sara N.; Jarrett, Kelsey; McIntyre, Tara; Bulinski, Joseph; Ownby, Stacy L.; et al. (American journal of human genetics, 2014)
Recently, we identified in two individuals with intellectual disability (ID) different de novo mutations in DEAF1, which encodes a transcription factor with an important role in embryonic development. To ascertain whether these mutations in DEAF1 are causative for the ID phenotype, we performed targeted resequencing of DEAF1 in an additional cohort of over 2,300 individuals with unexplained ID and identified two additional individuals with de novo mutations in this gene. All four individuals had severe ID with severely affected speech development, and three showed severe behavioral problems. DEAF1 is highly expressed in the CNS, especially during early embryonic development. All four mutations were missense mutations affecting the SAND domain of DEAF1. Altered DEAF1 harboring any of the four amino acid changes showed impaired transcriptional regulation of the DEAF1 promoter. Moreover, behavioral studies in mice with a conditional knockout of Deaf1 in the brain showed memory deficits and increased anxiety-like behavior. Our results demonstrate that mutations in DEAF1 cause ID and behavioral problems, most likely as a result of impaired transcriptional regulation by DEAF1.